Supply chain management mitigation to climate change in three selected industrial sectors - Bašić, Maja (Logistics, supply chain, sustainability and global challenges, 2023)
As the world economy is growing and globalisation is on the rise, climate change and its effects on the planet Earth are also increasing. But climate changes do not disturb only nature; they also affect businesses and their supply chains. Many companies have recently recognised the positive impacts of green and circular supply chain management practices. Supply chains that deliver products from around the world are increasingly exposed to the impacts of a changing climate and scarce resources. In this research, it was determined how climate change impacts supply chains in the food, automobile, and energy industry sectors. Furthermore, we wanted to find out if and how the management of supply chains is altered to adapt to the business environment which is more and more affected by environmental changes.
Keywords: circular economy; climate change adaptation and mittigation; krožno gospodarstvo; prilagajanje podnebnim spremembam; supply chain management; sustainable developement; trajnostni razvoj; upravljanje dobavne verige